A new Australian dream? Exploring associations between apartment design attributes and housing satisfaction in three Australian cities. (December 2022) - Kleeman, Alexandra; Hooper, Paula; Giles-Corti, Billie; Foster, Sarah
Abstract: Globally, compact city policies promote increased density to sustainably house urban populations. In Australia, the recent proliferation of apartments challenges an enduring cultural preference for detached housing, calling into question apartment residents' satisfaction with this housing form. We examined associations between apartment residents' ( n = 1082) housing satisfaction and perceived dwelling and building design attributes in 115 apartment developments in Perth, Melbourne and Sydney, and explored area-level disadvantage and city differences. Five design attributes (apartment space layout/function, acoustic and visual privacy, natural ventilation, and building security) were found to be significantly positively associated with satisfaction after adjustment for residents' demographic attributes, dwelling/neighbourhood self-selection factors and housing preferences, irrespective of area disadvantage or city. Moreover, residents who lived in their preferred housing type (e.g., they preferred a low-rise building and lived in this housing typology) reported significantly higher satisfaction than others ( p ≤0.001). However, few apartment dwellers lived in their preferred housing type, with the majority preferring a detached/semi-detached house. Our findings make a notable contribution to the evidence-base, indicating that apartment design policies with internal dwelling requirements that emphasise spacious, flexible layouts that promote comfort, privacy and security could better match the needs of apartment residents, leading to improved satisfaction. Highlights: The influx of new apartments in Australia challenges a cultural preference for houses. Apartment residents' satisfaction and perceived dwelling/building design were explored. Space, privacy, ventilation, and security were positively associated with satisfaction. Living in one's preferred housing type was positively associated with satisfaction. Policies that improve apartment design could increase resident satisfaction.